(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
An experiment to compare the performance of different solid-set sprinkler patterns was carried out during March and April 2004 in theDemonstration Farm of the Faculty of Agriculture, University ofKhartoum at Shambat. The experiment consisted of testing the effect ofsquare, rectangular and triangular sprinkler patterns on Christiansen’scoefficient of uniformity (CU%), uniformity of distribution (DU%) andwater loss (%) using the completely randomized design. The triangularpattern recorded the highest uniformity coefficient and uniformity ofdistribution and the lowest water loss. Water distribution uniformity(CU% and DU%) and water loss (%) were not significantly affected bysprinkler patterns. However, mean CU% and DU% had the followingdecending order: triangular pattern > square pattern > rectangular pattern,while mean values of water loss (%) was as follows: rectangular pattern> square pattern > triangular pattern.